Separate lives a comparative analysis of the parent-adolescent interpersonal communication in a disrupted family from the perspective of the adolescent - Suemith, Merlissa Elpedes 1977-
This study is a qualitative analysis of the communication process involved in the maintenance of the parent-child relationship in a disrupted family. It looked into the patterns of interaction and the factors that shaped such patterns. It compared the relationship of the relationship of the adolescent to both custodial and noncustodial parents. The framework of the study is relational perception and communication, with particular emphasis on the costs and rewards of relationship. The primary method used in the study was the focus interview supplemented with textual analysis of diaries written by the eight adolescent respondents belonging to disrupted families. Findings of the study reveal that adolescents are affected in negative ways by the separation of their parents. Depending on the adolescent's age and gender, marital separation results to juvenile delinquency, poor school performance and disobedience to parents. This becomes even more pronounced when their parent gets involved in extra-marital affairs or avail of a remarriage. However, adolescents adjust in a favorable manner if the separation helped to create a more peaceful atmosphere at home. It was also found out that boys are more vulnerable to post-separation problems than are girls and that they are more prone to developing negative perceptions of their parents. Between the parents, mothers were found out to be more involved in maintaining ties with their children. Fathers, on the other hand, tend to depend on the reactions of their children to their visits and relations. Adolescent self-disclosure is more bound to happen if the interactions are perceived by the child as rewarding interpersonally and materially. Otherwise, adolescents withdraw from both parents especially from the one that was more at fault in the separation. The adolescents disclose to their parents in differing degrees about their academics, financial needs, s personal views and social relations. Daughters tend to develop closer ties to their mothers than do sons. But whatever the case may be, children find themselves closer to their custodial parent than their noncustodial parent whether it is the mother or the father.